From Surakarta to Leiden: Transfer of Colonial Knowledge through Instituut voor de Javaansche Taal, 1832–1850 - Luthfah Eta ‘Aini; Muhammad Ibnu Majah (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
This article examines the Instituut voor de Javaansche Taal (IVJT), established in Surakarta in 1832, as an early institutional site of epistemic colonialism in Java. Building on the observation that, following the Java War (1825–1830), Dutch colonial power increasingly relied on the hegemony of knowledge rather than military coercion alone, this study asks how the IVJT institutionalized an asymmetric division of intellectual labor between European philologists and Javanese court literati, and how that asymmetry was subsequently transferred to Leiden and consolidated as the epistemic foundation of Dutch Indology. While existing scholarship has extensively examined Dutch Orientalism after the formal establishment of Indology as a university discipline at Leiden from the mid-nineteenth century onward, the earlier institutional history of the IVJT (1832–1842) as the empirical seedbed of that tradition remains comparatively under-examined, particularly through the combined analytical lens of Michel Foucault's power/knowledge and Edward Said's Orientalism. Using historical research methods (heuristics, source criticism, interpretation, and historiography), this study finds that the IVJT functioned as a colonial laboratory in which the collaborative labor of Javanese poets such as Ronggowarsito and Yasadipura III was systematically reclassified as native assistance rather than authorship, while European scholars such as F.C. Gericke and Taco Roorda retained exclusive scholarly recognition. The 1842 closure of the IVJT and the subsequent transfer of its manuscripts and philological apparatus to Leiden mark a concrete instance of epistemic transfer, through which colonial knowledge produced in Java became the institutional foundation of academic Indology in the metropole. The article argues that this genealogy has continuing relevance for contemporary decolonization-of-knowledge efforts in Indonesian historiography, insofar as it demonstrates how disciplinary infrastructures inherited from the colonial period continue to shape what counts as legitimate knowledge about the archipelago.